Beyond dietary therapy: addressing weight stigma awareness in medical students - Giuseppe Annunziata; Giordano Bruno Zonzini; Evelyn Frias-Toral; Raynier Zambrano-Villacres; Alexander Bertuccioli; Davide Sisti; Ludovica Verde; Daniele Di Pauli; Annamaria Colao; Giovanna Muscogiuri; Daniel Simancas-Racines; Alessandro Gennaro; et al. (Journal of Translational Medicine)
Abstract Background The growing prevalence of obesity worldwide has drawn increased attention to the issue of weight stigma. Discriminatory attitudes related to body weight are evident across various settings, including those that should ideally offer support to individuals with obesity, such as schools and sports facilities. This research aimed to examine weight-related stigma among university students enrolled in healthcare-related academic programs. Methods To measure weight stigma, researchers administered the Italian version of the Attitude Toward Obese Persons (I-ATOP) questionnaire to 201 students from the University of Urbino (Italy) and the University of Malaga (Spain). The analysis explored variations in stigma levels based on gender, BMI classification, nationality, Italian regional location, level of academic education, medical history, and lifestyle factors. Results The participant pool was predominantly female (58.2%) and Spanish (66.7%), with an average age of 22.86 ± 3.08 years and a mean BMI of 22.80 ± 3.25 kg/m2, placing most respondents in the normal weight range. Nearly half (47.8%) demonstrated a low degree of stigmatising attitudes. Within the sample, significantly lower stigma levels were reported among female and Spanish students (p = 0.001 and p = 0.011, respectively), as well as among those without a history of eating disorders (p = 0.017) and those who engaged in physical activity (p = 0.029). Additionally, stigma showed a notable decline in relation to higher educational attainment (p = 0.010). Conclusion This pilot study reveals the presence of weight stigma even within healthcare education settings, where future health professionals are being trained. These findings underscore the urgent need for comprehensive educational strategies aimed at fostering inclusive and nonjudgmental attitudes toward individuals with obesity. Importantly, the assessment and management of weight stigma should extend beyond nutritional therapy alone, recognizing its psychological, social, and structural dimensions. Integrating this broader perspective into healthcare curricula is thus essential to improve the quality of care for individuals living with one of the most prevalent and complex chronic conditions.